Rancang Bangun Sistem Informasi Desa untuk Meningkatkan Pelayanan Publik Kantor Desa Palewai - Suharsono Bantun; Jayanti Yusmah Sari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
As one of the government agencies in the region, the Palewai Village office cannot be separated from its responsibility to improve the quality of public services during the Covid-19 pandemic. Based on observations with the office, it is necessary to have an online system that can provide clear and up-to-date information, thus helping the public in obtaining information and services without having to come and gather in the service room. In addition, services with an online system will greatly help the people of Palewai Village during the pandemic. The online system in this service can be done by filling in the BPJS, KIS, SIM and SKTM cover letter forms from home so that people can avoid crowds in the service room as an effort to prevent the spread of Covid-19. The Village Information System can be implemented properly using HTML, CSS and Java Script for the interface, then using the MySql database and to connect the interface and database using PHP programming. The results of the evaluation carried out with a Likert scale and continuum line obtained a system feasibility value of 4.07 with a very feasible category to be applied.